3D numerical simulation on drilling fluid invasion into natural gas hydrate reservoirs. (15th February 2022) - Dong, Lin; Wan, Yizhao; Li, Yanlong; Liao, Hualin; Liu, Changling; Wu, Nengyou; Leonenko, Yuri
Abstract: The drilling fluid invasion into hydrate-bearing sediments (HBS) would trigger geological risks. However, invasion mechanisms and formation responses during drilling the gas hydrate reservoirs, especially the fluid-loss characteristics and control mechanisms of hydrate dissociation, remain poorly understood. Thus, we develop a three-dimensional (3-D) coupled thermal-hydro-chemical model to investigate the drilling fluid invasion process and dynamic responses of gas hydrate reservoirs. This model deals with the fluid-loss properties and flow field characteristics as well as well-formation interactions considering the effect of hydrate dissociation. The results indicate that the invasion characteristics mainly depend on drilling fluid pressure and permeability, while the temperature affects the hydrate dissociation. Besides, the fluid-loss velocity increases slowly after a sharp decrease at initial stage of invasion due to the increase of permeability induced by hydrate dissociation. Afterward, characteristics and mechanisms of drilling fluid invasion into hydrate reservoirs are determined by the invasion process coupled with hydrate dissociation. Given the unique characteristics of HBS, the invaded formation is divided into flushed zone, transition zone, and undisturbed zone, presenting a better description of the dynamic filtration process. Moreover, optimization strategies and drilling technology are proposed to prevent hydrate dissociation and control geological risks during drilling hydrate. Highlights: A three-dimensional (3-D) coupled thermal-hydro-chemical model is proposed. Characteristics of the flow field and fluid-loss velocity rely on fluid-rock interactions and phase change of hydrate. Mechanisms of drilling fluid invasion into HBS are discussed. This multi-field coupled process makes control, analysis, and prediction very difficult.